Analysis of Industrial Correlation Effect of Rare Earth Mining in China: Based on the 2010 Extended Input-output Table of China - Yu, Chen; Higano, Yoshiro; Mizunoya, Takeshi; Ge, Jian-Ping; Lei, Ya-Lin (Journal of Environmental Accounting and Management, 2026)
Researching the relationship between China’s rare earth mining industry and other sectors of the national economy may help to identify the role of the rare earth mining industry to promote the development of other key industries and enable the country to be more targeted in policy making for driving healthy development of the rare earth mining industry chain. This paper studies the relationship between the mining of rare earth and other sectors of the national economy, employing the method of inputoutput analysis based on the 2010 extended input-output table of China. The results demonstrate that the rare earth mining industry has a relatively small demand driving force for most industry sectors of China because the rare earth mining industry is an upstream raw material industry. The rare earth mining industry has a relatively high radiation effect for most industry sectors of China because the rare earth mining and dressing industry has a wide application in downstream industries. The rare earth mining and dressing industry belongs to the low demand driving force and low supply driving force types of industries, which means it has a low emissive power and low binding power. China should change the current export-oriented situation of the rare earth mining industry and focus input more on sectors such as metal mine mining, energy processing, equipment manufacturing, transportation and fuel power supply